EFFECTIVENESS OF THE REGULATION ON FINANCIAL SERVICE CONSUMER PROTECTION IN INDONESIA - Triyana Yohanes; Nikolaus Budi Arianto Wijaya (Penerbit Universitas Atma Jaya Yogyakarta, 2019)
Some cases of financial business transactions practices in Indonesia had caused financial damages were suffered by the consumers. Eventhough Indonesia had well regulated the protection of financial service cunsumers, in practices of dispute settlement oftently the concumers could not got fair solutions, so their rights could not be well fullfiled. The problem in this research was studied by a normative legal research, the data were analyzed by qualitative and comparative methods, and the conclusion was done by deductive method. From the analyzed data, it could be concluded that the effectiveness of the consumers protection in the sector of financial services business regulation in Indonesia was not high due to some reasons, such as, the weakness of the law enforcement, the OJK had not been pro-active in giving protection to the financial service consumers and the problem of legal culture of the Indonesian society.